Modular Upgradability in Consumer Electronics: Economic and Environmental Implications. (19th November 2015) - Agrawal, Vishal V.; Atasu, Atalay; Ülkü, Sezer
Summary: Modularly upgradable product designs have been advocated to offer environmental and economic advantages; however, they are not commonly used in the consumer electronics industry. In this article, we investigate the economic and environmental benefits and challenges of modular upgradability for consumer electronics. From an economic point of view, we posit that the limited adoption of modular upgradability in consumer electronics is owing to various demand‐, technology‐, and competition‐related issues. From an environmental point of view, we posit that modularly upgradable product designs may not necessarily lead to superior environmental outcomes. To reach meaningful conclusions regarding the environmental benefits of modular upgradability, one needs to understand how product architecture affects demand, production, and consumption patterns, which arise from endogenous consumer and manufacturer choices. It is also important to take into account that modular upgradability may have potentially differentiated effects in the production, consumption, and postuse phases of the lifecycle.